STUDY OD SOME FACTORS AFFECTING ON PRODUCTION CHARACTERS BUFFALO BREEDING IN NINEVAH PROVINCE - Basil A. Mahmood (Mesopotamia Journal of Agriculture)
The data is taken from (78) milch buffalo cows which are found on a private buffalo breeding farm in Ninevah province during the period from December 2001 to February 2004. The data were collected and analyzed to find the effect of parity and season of calving on total milk production, length of lactation, and dry period. The average of over-all were (2147kg; 281.230; 138.12 days) respectively. Results showed that parity had highly significant (p< 0.01) effect on over–all productive characters, so milk production increased with parity progressing from 1st to 7th calving. While length of lactation and dry period had decreased with progressing parity, the shortest averages were (257.87; 105.59) days respectively at 6th calving. Concerning calving season there was no significant on all productive characters.